2021
DOI: 10.7554/elife.59142
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary stem cells produce paracrine WNT signals to control the expansion of their descendant progenitor cells

Abstract: In response to physiological demand, the pituitary gland generates new hormone-secreting cells from committed progenitor cells throughout life. It remains unclear to what extent pituitary stem cells (PSCs), which uniquely express SOX2, contribute to pituitary growth and renewal. Moreover, neither the signals that drive proliferation nor their sources have been elucidated. We have used genetic approaches in the mouse, showing that the WNT pathway is essential for proliferation of all lineages in the gland. We r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 69 publications
1
24
1
Order By: Relevance
“…Integrating our neonatal mouse AP scRNA-seq dataset with the recently published data of fetal human pituitary (Zhang et al, 2020) revealed considerable overlap, including an analogous WNT landscape. A pronounced WNT profile has recently also been reported in the early-postnatal (2- weeks-old) mouse pituitary (Russell et al, 2021). Interestingly, this study showed a paracrine- regulatory role of these stem cells, stimulating neighboring committed progenitor cells (as well as stem cells) to proliferate and expand.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Integrating our neonatal mouse AP scRNA-seq dataset with the recently published data of fetal human pituitary (Zhang et al, 2020) revealed considerable overlap, including an analogous WNT landscape. A pronounced WNT profile has recently also been reported in the early-postnatal (2- weeks-old) mouse pituitary (Russell et al, 2021). Interestingly, this study showed a paracrine- regulatory role of these stem cells, stimulating neighboring committed progenitor cells (as well as stem cells) to proliferate and expand.…”
Section: Discussionmentioning
confidence: 78%
“…Very recently, it has been reported that stem cells in early-postnatal (PD14) pituitary can function as autocrine and paracrine signaling center, among others stimulating proliferation within the own stem cell compartment (Russell et al, 2021). Interestingly, when co-cultured, neonatal (PD7) AP organoids (as developed from WT mice) elevate the outgrowth of organoids from adult AP (as established from ubiquitously tdTomato(tdT)-expressing R26 mT/mG mice) (Figure 2D), coinciding with increased proliferation of the adult AP organoid-constituting stem cells, showing a Ki67 + index reaching the one of neonatal AP-derived organoids (Figure 2D).…”
Section: Resultsmentioning
confidence: 99%
“…Cell clusters were annotated manually using differential RNA expression of established pituitary marker genes. Key cell type markers included FSHB, LHB , and GNRHR for gonadotropes; GH1 for somatotropes; POMC for corticotropes; DIO2 for thyrotropes ( Cheung et al, 2018 ; Zhang et al, 2020 ); PRL for lactotropes; and SOX9 ( Rizzoti et al, 2013 ), LGR4 ( Russell et al, 2021 ), and RBPMS ( Cheung et al, 2018 ) for PSCs. A list of established markers used for the assignment of each cell type as well as markers identified in our datasets ( IQCJ-SCHIP1, NTNG1, EBF1, BNC2, ADGRA3 for PSCs) are listed in Table S2 .…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, expression of JUN and JUND , which have been implicated in the regulation of stemness in other tissues ( Pagin et al, 2021 ; Semba et al, 2020 ), was heterogeneous, with the highest expression associated with uncommitted clusters consisting mostly of male cells ( Figures 3B and 3C ). JUN has not been proposed as a PSC marker but was recently reported to be enriched in SOX2-positive cells through bulk RNA-seq in mice ( Russell et al, 2021 ). We therefore examined whether Jun showed co-expression with the stem cell marker Sox2 by mRNA in situ hybridization in male neonatal, juvenile, and adult mouse pituitaries.…”
Section: Resultsmentioning
confidence: 99%
“…This population has the ability to self-renew and to give rise to terminally differentiated pituitary cells, in vitro and in vivo [63,81,82,84], and in response to injury [85]. Additionally, they secrete paracrine signalling factors, including WNT ligands, which promote the generation of new endocrine cells from more committed neighbouring progenitors [86]. Thus, adult progenitor/stem cells appear to contribute to the plasticity of the pituitary gland both directly and indirectly, enabling adaptation and generation of new endocrine cells in response to physiological events or injuries.…”
Section: Developmentmentioning
confidence: 99%